The osteochondral autograft transfer system in hand surgery: a comprehensive evidence-based guide for the hand surgeon - Eisa, Amr; Aman, Martin; Panayi, Adriana C.; Harhaus-Wähner, Leila (Annals of plastic surgery, 2025)
Introduction - The Osteochondral Autologous Transfer System (OATS) is a surgical technique initially developed for knee procedures to address focal articular cartilage defects. Although widely applied in the knee, elbow, shoulder, and ankle, its application in hand surgery is limited but growing. This review aims to compile evidence-based insights into OATS for hand surgery, focusing on indications, technical nuances, outcomes, and donor-site morbidity. Additionally, a demonstrative case is presented showcasing the reconstruction of a capitate using OATS. - Methods - The systematic review followed PRISMA 2020 guidelines and was registered on PROSPERO. Electronic databases (PubMed, Google Scholar, Cochrane Library) and ClinicalTrials.gov were searched for studies up to August 1, 2024, using the keywords: OATS, osteochondral autologous transplantation system, hand, and wrist. Eligible studies included clinical applications of OATS in hand surgery with follow-up data. Case reports, series, and cohort studies were appraised for quality and risk of bias. Additionally, a narrative review addressed practical questions for hand surgeons. A demonstrative case involving capitate resurfacing during proximal row carpectomy was also included. - Results - Thirteen studies met the inclusion criteria, encompassing case reports and small series involving up to 11 patients. Indications for OATS in hand surgery included reconstruction of the lunate fossa, carpal bones, metacarpal heads, and interphalangeal joints. Favorable outcomes were reported, with donor sites including the lateral femoral condyle, medial femoral trochlea, and hemihamate bone. Donor-site morbidity was rare but included exertional knee pain and radiological degenerative changes. The demonstrative case highlighted capitate resurfacing with satisfactory functional and radiological outcomes. - Conclusions - OATS shows promise in addressing osteochondral defects in the hand, with favorable outcomes across various applications. Although evidence remains limited to small case series and reports, the technique demonstrates potential as a motion-preserving option. Future research should address donor-site morbidity in healthy knees and explore the feasibility of allograft use.
Gesehen am 28.01.2026